Strengthening National Insights Preventing Radicalism Towards a Nationalism-Conscious Nation in the Global Era (Case Study of Students of the Faculty of Social Sciences, State University of Medan) - Damanik, Denda; Surbakti, Fina Afrillia; Mufidah, Anisah; Pratiwi, Dina; Mustika, Fanny; Ivanna, Julia (Journal of General Education Science, 2023)
National insight is something that cannot be separated from the life of every Indonesian citizen. This is because national insight is part of the understanding of citizenship. Therefore it is important to strengthen and also develop national insights for the younger generation who continue to experience changing times which are increasingly global or in the global era. This article or article by the author aims to find out about how to strengthen national insights to prevent radicalism towards a nation that is aware of nationalism in the global era. As for the type of research conducted by the author, namely qualitative research, then using data collection techniques, the author used the method of observation and interviews with students of the Faculty of Social Sciences, Medan State University. Based on the results of the research, the strengthening of national insight among the younger generation or students in an effort to defend this republic from the threat of radicalism can be implemented through character education through Citizenship Education subjects or courses, this is because Citizenship Education plays an important role in strengthening the implementation of good education. national in mind.